INSTITUTIONAL ENSURING THE TRANSFORMATION OF THE FINANCIAL MECHANISM FOR THE DEVELOPMENT OF HOUSING CONSTRUCTION IN CONDITIONS OF INSTABILITY - Yevtushenko , Yu. V. (The actual problems of regional economy development, 2024)
The article is devoted to the study of the role of institutional support for the transformation of the financial mechanism in stimulating the development of housing construction in conditions of instability of the external environment. The leading role of the institutional environment in ensuring housing construction processes in the country is substantiated. It is proven that the historical development of mankind was constantly accompanied by the need to provide housing for every individual, and therefore by dynamic institutional transformations, which were aimed at improving the relevant mechanisms, among which the financial mechanism for the development of housing construction occupies an important place. Based on the generalization of the scientific approaches of scientists and practitioners, the semantic profile of the category "institutional support" was investigated, which created an opportunity to propose an author's approach to the interpretation of the scientific category "institutional support of the financial mechanism for the development of housing construction", which should be understood as the organization of the activities of the relevant institutions in terms of development, implementation and application of a set of norms and rules of financial behavior of participants in the housing market, necessary to satisfy their financial interests, ensure a sufficient volume and continuous renewal of the country's housing stock. It has been proven that the basis of innovative development of housing construction should be a combination of dominant formal and informal institutions, which will allow to determine the target trajectory of the development of the financial mechanism of housing construction in the country in modern conditions, will contribute to meeting the needs and interests of all its participants. A graphical interpretation of the dependence of the level of institutional support of the financial mechanism of the development of housing construction and the state of the housing stock is offered. The leading role of institutional support of the financial mechanism in the process of housing construction, stimulation of the development of the national economy and preservation of state sovereignty is substantiated. The need to deepen methodological approaches to the development of institutional support for the financial mechanism of housing construction as an important component of ensuring the economic security of the state is emphasized.